Management of pilonidal sinus disease with Limberg flap: our experience - Singh, Mahavir; Dalal, Saish; ., Baleshwar; Raman, Sethu (International Surgery Journal, 2020)
Background: Pilonidal sinus disease is a common disease of young adults. The management of the sacrococcygeal pilonidal sinus varies from conservative measures to various surgical procedures. The main concern for the treatment to the patient is the recurrence. Although several methods have been described all have been associated with high recurrence rates. This study was carried out to evaluate the advantages, results of rhomboid excision and limberg flap reconstruction in the management of pilonidal sinus disease. Methods: This prospective study was conducted in General Surgery department of a tertiary care centre of Haryana. It includes 29 patients who were treated for pilonidal sinus disease by Limberg flap surgery from January 2015 to January 2019. Results: All patients were successfully treated with minimal postoperative discomfort. Only two patients developed seroma which was managed conservatively and in two patients there was slight flap tip necrosis which was also managed conservatively. Rest all other patients wound healed nicely with minimal scarring, with very less postoperative pain, with no recurrence so far. Conclusions:Limberg flap is very effective treatment for pilonidal disease. It has many advantages as it is easy to perform and design, and it flattens the natal cleft with large vascularized pedicle, sutured without tension. This in turn maintains good hygiene, reducing the friction, preventing maceration, and avoiding scar in the midline. The technique is easy to perform in quick time, useful in both primary and recurrent diseases, with very low complication and recurrence rate. Other advantages are quick healing time, short hospital stay, and early return to daily life.